Cytogenetic Studies On The Water Buffalo (Bubalus Bubalis) - Abdullah, Mohamad Hilmi (1984)
Chromosome analysis was undertaken on Murrah,swamp , F1 (Murrah x swamp ) and backcross (F1 female x Murrah male) buffaloes (Bubalus bubalis) using a modified leucocyte culture method combined with Giemsa (G) constitutive heterochromatin (C) and nucleolus organiser region (NOR) banding procedures . A combination of 80% medium RPMI 1640 , 20% calf serum , pokeweed mitogen and buffy coat gave many good quality metaphases . The Murrah , swamp and F1 buffaloes had chromosome complement s of 2n = 50 , 2n = 48 and 2n = 49 respectively . The Murrah karyotype had 5 pairs of submetacentric chromosome s and 20 pairs of acrocentric chromosomes while the swamp karyotype had 1 pair of large metacentric chromosomes , 4 submetacentric pairs and 19 pairs of acrocentric chromosomes. /F1 hybrid had an intermediate karyotype. Nine backcross animals had a 2n = 49 complement while 3 backcross animals had a 2n = 50 complement.